Janeway's immunobiology - Kenneth M Murphy (Garland Science/ Taylor & Francis Group, 2016)
Janeway's Immunobiology is a textbook for students studying immunology at the undergraduate, graduate, and medical school levels. As an introductory text, students will appreciate the book's clear writing and informative illustrations, while advanced students and working immunologists will value its comprehensive scope and depth. Janeway's Immunobiology presents immunology from a consistent point of view throughout-that of the host's interaction with an environment full of microbes and pathogens. The Ninth Edition has been thoroughly revised bringing the content up-to-date with significant developments in the field, especially on the topic of innate immunity, and improving the presentation of topics across chapters for better continuity.